Removal of Petroleum from Aqueous Systems by Poly(divinylbenzene) and Poly(methyl methacrylate-divinylbenzene) Resins: Isothermal and Kinetic Studies - Silva, Carla; Rocha, Paulo; Aversa, Thiago; Lucas, Elizabete (Видавництво Львівської політехніки, 2019)
та дивінілбензенова (ДВБ) смоли для адсорбції нафти в штучному середовищі нафта-вода. Дослідження проводили для двох процесів: (i) безперервний процес для оцінювання кількості води з нафтою, яку можна елюювати до досягнення межі насичення смол; і (ii) періодичний процес для одержання кінетичної та ізотермічної моделі двох смол., Встановлено, що для обох смол результати найкраще відповідають ізотермі Фройндліха та кінетичній моделі псевдодругого порядку. Знайдені значення низької енергії активації свідчать про фізичну адсорбцію між смолами та нафтою. Показано, що незважаючи на непогану ефективність ДВБ смоли щодо видалення нафти, її можна замінити промисловою смолою MMA-ДВБ, завдяки таким перевагам як менша вартість, токсичність та легкість регенерації.

In this study, the performance of two polymer resins was evaluated, one composed of methyl methacrylate-divinylbenzene (MMA-DVB) and the other of only divinylbenzene (DVB), for adsorption of oil in synthetic oily wastewater. The tests were carried out using two processes: (i) continuous flow, to assess the quantity of oily water that can be eluted until reaching the saturation point of resins; and (ii) batch, to obtain information about the best-fitting kinetic and isotherm models for the two resins. The results for both resins showed better fits to the Freundlich isotherm model and the pseudo-second-order kinetic model. The low activation energy values found suggest physical adsorption between the resins and oil. Although DVB resin has presented slightly better oil removal efficiency than the MMA-DVB one, the results showed that DVB resin can be industrially replaced by MMA-DVB resin, due to the latter advantages: lower cost, lower toxicity and easy regeneration, as indicated by the kinetic and isothermstudies.
Видалення нафти з водних систем полідивінілбензеновими та поліметилметакрилат-дивінілбензеновими смолами: ізотермальні та кінетичні дослідження
Keywords: оброблення нафтовмісної води; адсорбція; пористі полімерні смоли; ізотерма; кінетична модель; oily water treatment; adsorption; porous polymer resins; isotherm model; kinetic model